TRAUMA TAKUT KEHILANGAN DALAM CERITA FILM BILA ESOK IBU TIADA (KAJIAN PSIKOANALISIS) - Arif Rahman; Missriani; Muhammad Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and analyze: 1) the symptoms of fear-of-loss trauma displayed by the characters in the film; 2) the psychological dynamics of the characters based on psychoanalytic theory; 3) the impact of trauma on the characters’ behavior, dialogue, and social relationships; and 4) the symbols or scenes that represent the trauma of loss in the film. This research employs a qualitative descriptive approach using Sigmund Freud's psychoanalytic theory, particularly focusing on the concepts of the unconscious, defense mechanisms, and the connection between past trauma and character behavior. The analysis reveals that the main character in the film exhibits several forms of defense mechanisms such as repression, regression, and projection as responses to the fear of losing the mother figure. The study concludes that Bila Esok Ibu Tiada effectively portrays the trauma of fear of loss as a profound internal conflict and offers deeper insight into the psychological impact of losing a mother figure on one’s identity and emotional structure.